Comparison of the Antioxidant Activity of Volatile Compounds of Traditional Herbal Waters Per Serving Cup: Antioxidant activity of traditional herbal waters - Reza Tabaraki; Negar Sadeghinejad (Iranian Journal of Pharmaceutical Sciences, 2024)
Herbal water is referred to the liquid obtained from the distillation of medicinal plants. Different parts of plants, such as flowers, fruits, leaves, seeds and roots have long been used to produce herbal waters. Herbal waters are used as dietary supplements and alternative medicine and are commonly used for flavoring in baking. Previous studies focused on the non-volatile constituents of herbs. However, plants also contain numerous volatile chemicals. Therefore, antioxidant capacities of 20 Iranian herbal waters were assessed by FRAP, DPPH and TEAC assays, and their total phenolic contents measured by Folin–Ciocalteu assay. These herbal waters exhibited a broad range of antioxidant activities, varying from 0.18 to 3.20 mmol Fe2+/l in the FRAP assay, 91.43-94.99% inhibition in the DPPH assay, 19.27-28.79 mg trolox equivalent/ml in the TEAC assay and 2.90-132.51 mg gallic acid equivalent/l in total phenolic content. Classification of Iranian herbal water was performed by cluster analysis and principal component analysis and four groups were recognized based on antioxidant activity and total phenolic content. Rose, thyme, summer savory and mint herbal waters were screened as the highest antioxidant activity and total phenolic content.